Implementation of Learning Theory of Constructivism Perspective Jean Piaget (1896-1980) in PAI Learning at SDI Bilal Bin Robah Batulayar Village, Batulayar District - Nurul Aeni; Ahmad Budiamin; Fathurrahman Muhtar (Universitas Muhammadiyah Enrekang, 2023)
This research is about Jean Piaget's constructivism learning theory. The type of research used in this study is field research because researchers have to go directly into the field and be involved with local schools. This study describes the theory of constructivism in learning. Constructivist epistemology is a theory that describes the way a person obtains knowledge by constructing that knowledge within himself, without waiting or expecting the transfer of knowledge from others or educators (teachers). Researchers conclude that Piaget's perspective constructivism learning theory is a learning process that gives freedom to students in constructing the knowledge that exists within them. Each theory has advantages and disadvantages in its implementation, as well as advantages and disadvantages of constructivism theory in learning. The right solution to complement these shortcomings is for teachers to be able to make changes in the learning model and add insight and knowledge in order to implement constructivism theory in the learning process. In conclusion, the theory of constructivism at SDI Bilal bin Robbah has not been able to be applied in all classes because there are obstacles that there are students who cannot read, especially in grades 1 and 2. The solution to overcome these difficulties is that SDI Bilal bin Robbah teachers create a program called Diniyah Sore, where students practice reading. In contrast, in grades 3 and 4, it can be implemented properly because students can read and seek literacy on their own with teacher guidance.